Identification of poymorphism and association analyses of FMO3 gene related with carcass and meat quality in Cihateup Duck - Anggraeni, Anggraeni; Gunawan, Asep; Rukmiasih, Rukmiasih; Suryati, Tuti; Sumantri, Cece (ANIMAL PRODUCTION, 2017)
The aim of this study was to identifypolymorphism and association of the FMO3 gene related to carcass and meat quality in Indonesian Cihateup ducks. A total of sixty Indonesian Cihateup ducks were used in this study. Tissues from breast muscleswas used for genomic DNA. Association analysis showed that the SNP g.849A>G was highly significantly associated (P<0.01) with live weight (LW), carcass weight (CW), breast muscle weightÂ  (BMW), pH, cooking loss, drip loss (DL), lightness (L*) and redness (a*), TBARS and TMA. Compared to the GG genotype, the AG genotype exhibited greater levels (P < 0.05) LW, CW, pH, a*, TBARS and TMA but not DL and L*.Â  These results will improve the understanding of the functions of the FMO3 gene in carcass and meat quality within the liver and will shed light on FMO3 as a candidate gene in the selection of ducks with good carcass and meat quality traits